Evaluasi Hasil Belajar Mahasiswa dengan Pendekatan Bleended Learning Berbantuan E-Learning UNP - Syaifullah, Lasyatta; Dermawan, Andri; Jalinus, Nizwardi (Southeast Asian Journal of Technology and Science, 2021)
This study aims to measure the extent of the level of success and mastery of students against competencies in learning Automotive Electronics by using experimental methods. The subjects in this study were students of the Automotive Electronics Electricity course with a sample size of 30 students consisting of control class (class A) and experimental class (class B) as primary data. The data analysis technique is the analysis requirement test, namely the normality test using the SPSS program with the Kolmogorov-Smirnov test and the homogeneity test, then the Independent T-Test is then carried out to measure the extent of the level of success and mastery of students against competencies in learning Automotive Electronics. Based on the data that has been obtained, the evaluation of student learning outcomes with the UNP e-learning-based blended learning approach is able to measure the extent of the success rate and mastery of students of competencies in learning Automotive Electronics so that it can provide an overview for lecturers to plan learning strategies in other lessons